2015
DOI: 10.4209/aaqr.2014.11.0275
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Peroxyacetyl Nitrate at a Background Site in the Pearl River Delta Region: Production Efficiency and Regional Transport

Abstract: Peroxyacetyl nitrate (PAN) is a trace constituent of the atmosphere but plays important roles in air pollution and atmospheric chemistry. To understand the chemical and transport processes of PAN in the Pearl River Delta (PRD) region, measurements of PAN, its precursors and related parameters were made at a regional background site in late summer and late autumn of 2011. Despite the fairly low ambient levels of PAN in general, several photochemical episodes with peak concentrations of PAN and ozone (O 3 ) as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…These levels were lower than those measured at urban and suburban areas in Beijing [8,9,13], and an urban site in Lanzhou in western China [7]. Compared to other field measurements in the PRD region, the mixing ratios of PAN at the BGS site were lower than those observed at the regional background site (the Hok Tsui site, measurement in 2011) [12] and the downwind rural site in the PRD region (the Heshan site, measurement in 2012) [18], which were mainly influenced by the outflow air masses from the center PRD region. The variations of PAN levels in different field measurements were mainly related to the variations of its precursors.…”
Section: Description and Configuration Of Community Multiscale Air Qucontrasting
confidence: 63%
See 2 more Smart Citations
“…These levels were lower than those measured at urban and suburban areas in Beijing [8,9,13], and an urban site in Lanzhou in western China [7]. Compared to other field measurements in the PRD region, the mixing ratios of PAN at the BGS site were lower than those observed at the regional background site (the Hok Tsui site, measurement in 2011) [12] and the downwind rural site in the PRD region (the Heshan site, measurement in 2012) [18], which were mainly influenced by the outflow air masses from the center PRD region. The variations of PAN levels in different field measurements were mainly related to the variations of its precursors.…”
Section: Description and Configuration Of Community Multiscale Air Qucontrasting
confidence: 63%
“…Since PAN was first discovered in photochemical smog in Los Angeles in the 1950s, numerous studies have investigated the distribution and source contributions of PAN through field measurements and model simulations [3][4][5][6]. The characterization includes the abundance of PAN, the relationship with its precursors, and the contributions of regional transport in different environments.The spatial variations of PAN and its formation mechanism has also been investigated in China, including urban, suburban, rural, and remote areas, for example, in Lanzhou [7],, and in the Pearl River Delta (PRD) region [11,12]. Zhang et al [13] found that the thermal decomposition dominated PAN removal in urban environments in Beijing, from June to September 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the Loess Plateau region, the data points are scattered from the lower left all the way to the upper right, because of mixed particles from anthropogenic pollution and natural dust. The data points in the Pearl River Delta show a similar scattered pattern but with a higher color ratio than those of anthropogenic pollution aerosols, because of the existence of a fraction (about 20 %) of larger-sized marine sea salt aerosols (Xu et al, 2015).…”
Section: Aerosol Optical Properties Over the Representative Regionsmentioning
confidence: 77%
“…Also, the North China Plain contains anthropogenic dust year-round and transported natural dust in spring (Logan et al, 2013;. The air quality and pollution dispersal over the Pearl River Delta are controlled by specific meteorological conditions, and the Pearl River Delta aerosols are dominated by anthropogenic pollution and a small fraction of marine aerosols (Hara et al, 2011;Xu et al, 2015).…”
Section: Study Regionsmentioning
confidence: 99%